1992
DOI: 10.1161/01.cir.86.2.494
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aging, sex, and physical training on cardiovascular responses to exercise.

Abstract: A lower stroke volume, heart rate, and arteriovenous oxygen difference at maximal exercise all contribute to the age-related decline in VO2max. Effects of age and training on VO2max, maximal cardiac output, and stroke volume cannot be fully explained by differences in body composition. In sedentary subjects, however, the sex difference in maximal cardiac output and stroke volume can be accounted for by the greater percentage of body fat in women than in men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

50
402
6
4

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 547 publications
(462 citation statements)
references
References 36 publications
50
402
6
4
Order By: Relevance
“…Consistent with our findings, Seals et al 27 failed to demonstrate an increase in maximal cardiac output despite effective exercise training in subjects averaging 63 years of age. This contrasts with the findings of several previous longitudinal studies in young 6,13,28,29 and old 6,29 subjects. Differences in selection and screening of normal subjects, training methods, and measurement techniques offer plausible explanations for these discrepancies.…”
Section: Exercise Trainingcontrasting
confidence: 99%
See 1 more Smart Citation
“…Consistent with our findings, Seals et al 27 failed to demonstrate an increase in maximal cardiac output despite effective exercise training in subjects averaging 63 years of age. This contrasts with the findings of several previous longitudinal studies in young 6,13,28,29 and old 6,29 subjects. Differences in selection and screening of normal subjects, training methods, and measurement techniques offer plausible explanations for these discrepancies.…”
Section: Exercise Trainingcontrasting
confidence: 99%
“…1,2 This decline is proportional to a decreased cardiac output reserve, peak heart rate, and peak stroke volume in older subjects. [3][4][5][6] The age-associated decline in maximal oxygen consumption can be attenuated by habitual aerobic exercise, although the mechanism is unclear. [7][8][9][10][11] Although it has been shown that exercise training can augment both cardiac output and the AV oxygen difference in younger subjects, 12,13 these components have not been measured in older subjects before and after exercise intervention.…”
mentioning
confidence: 99%
“…Regarding gender, the slightly higher COP values found in women are probably related to the fact that they have lower values of VO 2 max 37 and ventilation, when compared to men, remembering that, as with the equations 26,38,39 that predict ventilatory variables at resting spirometry, body size is taken into account and typically women are smaller than men.…”
Section: Discussionmentioning
confidence: 98%
“…Typically, maximal oxygen consumption (VO 2max ) falls steadily from 35 to 40 years of age at a rate of ∼10 % per decade (Fleg et al 2005;Hawkins and Wiswell 2003;McGuire et al 2001a;Ogawa et al 1992;Tanaka and Seals 2008). Although this decline in aerobic capacity with increasing age is often considered to be inevitable, it seems that this fall can be decelerated, maintained, or even reversed in the elderly by maintaining a high level of physical activity (Faulkner et al 2008;Fujimoto et al 2010;Grimsmo et al 2010;Heath et al 1981;McGuire et al 2001b;Murias et al 2010;Osteras et al 2005;Posner et al 1986;Rogers et al 1990;Trappe et al 2013;Trappe et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, by experimental design, despite knee-extensor exercise demanding far less than maximal cardiac output in both groups, the elderly exhibited attenuated blood flow which was compensated for by a higher arterio-venous oxygen difference (a-vO 2diff ) (Lawrenson et al 2004). It is possible that this alternative approach to achieve the same VO 2 in the old is an advantageous adaptation related to limited O 2 transport and more specifically the age-induced decline in maximal cardiac output (Hagberg et al 1985;Ogawa et al 1992). Surprisingly, to our knowledge, there has not been a study that investigated the impact of aging on the plasticity of whole body exercise capacity in young and old subjects with the same initial levels of VO 2max .…”
Section: Introductionmentioning
confidence: 99%